(untitled) (Sains Humanika, 2020)
Environmental sustainability of a developed nation is not only measurable from the aspect of infrastructure development and its public utility. However, the mainstay is the cleanliness, beauty and universal well-being through the use of green technology by 2050. This study is conducted in a qualitative study using a holistic single case study design involving Compound Steel Case. on a kindergarten in the state of Perak. Participants of the study involved in this study consisted of a focus group consisting of 18 children and an educator. The survey data was obtained through triangulation results from unstructured interviews, observations and documents. Overall, the findings show that the way children handle waste management issues is to produce compost fertilizers through project activities. In fact, the final product produced by children is the process of planting mulberry trees and worm terrarium using compost fertilizer produced.